Factors Related to Malnutrition in Children Under Five at Kori Public Health Center - Novia Katupu; Honey Ivone Ndoen; Ribka Limbu (Lontar : Journal of Community Health, 2021)
Malnutrition is currently an unsolved health problem in the work area of Kori Public Health Center, the incidence of malnutrition has increased from 2017-2019. This is a case-control study that aimed to determine parenting, history of infectious diseases, family income, number of family members related to malnutrition in children under five. The sample size is 51 for each case and control. The dependent variable is malnutrition and the independent variables are parenting, history of infectious diseases, family income, and the number of family members. The results show that parenting (p-value 0.004 and OR 12,583), history of infectious diseases (p-value 0.000 and OR 8.854), and family income (p-value 0.000 and OR 10,382) are related to malnutrition of children under five. Parenting is the most influential variable so that Kori Public Health Center should provide counseling to the mothers, especially the mothers of malnourished children, about health care including supplying nutritious food for children.